Development of Dachl Cross-Cultural Learning Designs - Lilis Afifah; Dewi Kartika Ardiyani; Edy Hidayat; Sawitri Retnantiti (BRILIANT: Jurnal Riset dan Konseptual, 2021)
The actualization of learning materials needs to be done to create a learning situation that is under the times. In learning German as a foreign language, the concept of DACHL has not been well recognized by every German teacher at the SMA / MA / SMK level. For this reason, adjustments to learning materials, techniques, and learning strategies are considered important so that the German learning process does not only train language skills but also fosters a cross-cultural understanding of these countries and the Indonesian nation itself. This article attempts to describe the results of training activities for the preparation of cross-cultural learning designs for German language teachers at the SMA / MA / SMK levels throughout Malang and its surroundings. This training implementation method which is accommodated in community service activities is designed by adopting an education and training system for ASN, namely on campus and off-campus. Despite undergoing method modifications as a result of the outbreak of the Covid-19 pandemic, training is going well. With simultaneous mentoring, collaboration, and collaboration between various parties, participants can receive the material well and simultaneously apply it in the form of a learning design.